Impact of Big Data Analytics on Audit Quality With Audit Delay as Mediator - Angga Bayu HARYANTO; Edi SETIAWAN (International Journal of Environmental, Sustainability, and Social Science, 2024)
This study investigates the impact of using Big Data Analytics on the quality of audits and the time it takes to complete audits in fintech companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. Using a purposive sampling method, data from 20 companies were analyzed to assess the impact of Big Data Analytics on these factors. The results indicate that using Big Data Analytics reduces the time it takes to complete audits but does not directly impact the quality of audits. Furthermore, research has demonstrated that audit delay has a detrimental effect on the quality of audits, suggesting that extended delays might undermine the results of audits. However, the presence of audit delay does not mediate the effect of Big Data Analytics on audit quality. This implies that the advantages of Big Data Analytics in audit quality are relatively unaffected by delays. These findings highlight the importance of utilizing Big Data Analytics to improve the efficiency of audits. However, the impact on audit quality may be restricted, offering valuable information for improving audit procedures in the fintech sector.